The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1186/s12877-015-0098-9
|View full text |Cite
|
Sign up to set email alerts
|

Re-assessing the dimensional structure of the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE): empirical evidence for a shortened Brazilian version

Abstract: BackgroundThe dimensional structure, effective number of item responses and item redundancies are controversial features of the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) requiring more light. The aims of the present study are to revisit the dimensional structure and propose a shorter version of the instrument.MethodsThe sample comprised 652 elderly and their informants, either attending a geriatric service of a public university clinic or enrolled in a health care provider database i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
1
0
2
Order By: Relevance
“…Studies in non-stroke populations rarely found low scores since aging is usually associated with stable or declining cognition. 27 Mistakenly scoring early recovery after stroke as improvement might explain these low scores. Patients with low scores were younger and young patients are more likely to improve after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in non-stroke populations rarely found low scores since aging is usually associated with stable or declining cognition. 27 Mistakenly scoring early recovery after stroke as improvement might explain these low scores. Patients with low scores were younger and young patients are more likely to improve after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…O estudo FIBRA-RJ, deu origem a uma série de artigos, dissertações de mestrado e teses de doutorado. 3,12,[28][29][30][31][32][33][34][35][36] Discussão O estudo FIBRA-BR, por seu delineamento multicêntrico, provavelmente representou um dos esforços mais abrangentes de pesquisadores brasileiros, para a compreensão da dimensão da fragilidade e seus fatores associados, em território nacional. O segmento Rio de Janeiro desse estudo, o FIBRA-RJ, representou uma tentativa de ir além dos objetivos inicialmente traçados, e dar continuidade ao acompanhamento da amostra examinada, investigando outros aspectos de acometimento de saúde, bastante comuns entre a população idosa, e ainda carentes de estudos populacionais com um número substancial de indivíduos.…”
Section: Resultsunclassified
“…Além disso, alguns instrumentos de avaliação geriátrica foram abordados do ponto de vista da sua adaptação transcultural para o Brasil. 12,35,36 Se tais estudos têm conhecida limitação, associada à causalidade reversa, que impede conclusões seguras acerca da ordem cronológica dos fenômenos, no entanto, eram necessários, uma vez que, até então, poucos trabalhos descreviam tais condições na população brasileira.…”
Section: Resultsunclassified